Investigação sobre política de indexação: bibliotecas da área da saúde da UFPA - FONSECA, Luciana di Paula Andrade (2020)
It is about on investigation on indexation policies in libraries of the area of the health of the Universidade Fedral do Pará (UFPA). And the relevance of an indexation policy is verified for the indexation process from stages that characterize the subject analysis: documentar reading, identification and selection of concepts for the representation of the information. It analyzes the non standardization of the indexation procedures in the libraries of the health area of UFPA. In this field, it is had as general objective: To contribute with discussions and reflections on indexation policies in the university libraries; and and is divided in three specific objectives: a) Conduct theoretical survey on indexation and indexing policy in academical libraries; b) to Investigate the elements of the indexation policy applied in the sectoral of libraries of the health area of UFPA; c) to Discuss the strategies of use of the elements of indexation policies between the sectorial libraries of the health area and coordinating library of SIBI-UFPA. For the methodological development, is divided in two stages, being used as instruments for the collection of data the questionnaire and a half structured interview in a field research with four librarians of four sectorial libraries of the health area. The questionnaire as instrument of field research is fast and objective, starting from him it was obtained the first methodological stage and the second stage is the half structured interview, applied with the unit of information that coordinates the System of Libraries of UFPA. The results obtained in the collection of data evidence the absence of indexation policies in the sectorial libraries of the health area of UFPA and in the coordinating library of SIBI-UFPA. Thus, the creation of guidelines to orientate the indexation process in the academical libraries is important for the standardization in the stages of the indexation process, optimization of the system of recovery of the information and the progress in the development of studies about the indexation theme and indexation policy.